Estudio de factibilidad para la creación de una empresa dedicada a producir y comercializar harina del raquis o vástago del plátano hartón dominico en el departamento del Quindío (2014)
The project is carried out under the line of business research, relevant to the Business Administration program, where it will be aimed at the generation of business strategies, supported by theories of competitive advantage of Michael Porter and the Classical Theory of Fayol's Administration. The study was carried out through a market investigation which showed the large number of people who include flour in their diet, on the other hand there was an oversupply of flours in the department of Quindío, but not one was identified that has High nutritional value such as Banana Stem Flour. Subsequently, the technical, organizational and legal, environmental and financial study was conducted, where the weaknesses and strengths of the production and commercialization of Racine Flour or Banana Kindred in the market were identified; additionally, hierarchies and organizational responsibilities were determined, through the organizational chart of the company, in the same way, legal aspects were analyzed in terms of the type of society that is going to be implemented and what is the regulation that the company must comply with according to the object social of it, finally determined the pros and cons of the creation of the company, and all the requirements for the implementation of it